2005
DOI: 10.1597/03-142.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Esthetic, Functional, and Quality-of-Life Outcome in Adult Cleft Lip and Palate Patients

Abstract: Surgery of the lip and nose appears to be of prime importance for patients with a cleft lip and palate. Cleft patients who do not request secondary treatment are not always satisfied with the treatment. Patients with realistic expectations in regard to further treatment should be treated by specialists, whereas those with unrealistic expectations should be referred to a clinical psychologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
201
8
20

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(246 citation statements)
references
References 20 publications
17
201
8
20
Order By: Relevance
“…Patients with CLP who are dissatisfied with their facial appearance may be at increased risk of developing social problems and withdrawal [12,13]. It is well known that the quality of the reconstructive and supportive procedures that an individual with a chronic health condition receives can have an impact on their health-related quality of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CLP who are dissatisfied with their facial appearance may be at increased risk of developing social problems and withdrawal [12,13]. It is well known that the quality of the reconstructive and supportive procedures that an individual with a chronic health condition receives can have an impact on their health-related quality of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CLP has a negative impact on the patient's QoL (16)(17)(18). The difficulties relate to dissatisfaction with facial appearance, lower levels of self-esteem, and experiences of discrimination in employment and social settings (19).…”
mentioning
confidence: 99%
“…Children later require special dental or orthodontic care, speech therapy, as well as social and psychological services. The optimal management protocol entails a range of services that need to be provided in a coordinated manner from birth into adolescence and sometimes adulthood stages [35][36][37][38][39].…”
Section: Prevention and Intervention Strategiesmentioning
confidence: 99%